Student responses on the survey of global competence in PISA 2018. Issue 4 (4th July 2022) - Chandir, Harsha
ABSTRACT: 'Global Competence' (GC) is currently being visualized by international and national bodies as an education imperative. Not only has GC become ubiquitous as a policy idea, it is, in 2018, being assessed by the Organization for Economic Cooperation and Development's (OECD) Programme for International Student Assessment (PISA). PISA has quantified the multifaceted concept of GC into a series of measurable and comparable constructs. Using concepts from (Science and Technology Studies) STS, the aim of this paper is to explore how a selection of students in Victoria understand and respond to the assessment of global competence in PISA 2018. The methodology of 'survey encounters' was employed to elicit students' thinking as they encountered the questions on the survey. While the PISA survey was developed to test the students, the methodology of 'survey encounters' also provided an opportunity for the students to test the PISA survey.